PENGARUH MEDIA PEMBELAJARAN PUZZLE TERHADAP MOTIVASI BELAJAR PADA MATA PELAJARAN IPA KELAS IV DI MI PUI HEGARMANAH LEUWILIANG BOGOR TAHUN PELAJARAN 2022/2023 - DAMAYANTI, RESTI (INSTRUKTUR INSTRUKTUR: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2024)
The learning  results of class  IV at MI PUI Hegarmanah are categorized as very low due to several factors , so that students are less enthusiastic in the learning process.  This type of research used is quantitative research. The research instrument used the validity test and instrument reliability test. Descriptive statistical analysis is used in the method of data analysis. The aftereffects of information examination. The results of data analysis on student motivation variables regarding Puzzle Learning Media stated that most of the fourth grade students of MI PUI Hegarmanah totaling 33 students had good motivation. Furthermore, the consequences of information investigation of understudy learning motivation have a good level seen from the questionnaire distributed by researchers, as many as 4 students (12%) have low motivation, as many as 15 students (46%) have moderate motivation and 14 students (42%) have high motivation